The family doctor in the face the occurrence of abusing of the alcohol by patients - Trnka, Jakub; Susło, Robert; Drobnik, Jarosław (Przewodnik Lekarza/Guide for GPs, 2010)
The problems connected with the abuse of the alcohol beverages refers doctors of many specialties. There appears also in the family doctor practice. The family doctor gets familiar with different forms of abusing of alcohol beverages in his own patients, from the mildest form until the extreme form, that is named the alcoholic disease. Many patients hide before the doctor their alcoholic problem. Symptoms caused by an alcohol abuse are referred by the patient as illness symptoms. It can also take place that the patient will come to the family doctor with the extreme form of the alcoholic disease, with the blue devils. It is an illness severely threatening the patients life, with large percentage mortality. The correct diagnosis of beginning delirium tremens and initiating of the suitable treatment can save the patients life. It happens many times that symptoms of beginning delirium deceived are misinterpreted with other illnesses of the individual. A separate problem are patients who are family members of people abusing alcohol beverages.